Statelessness, Trauma and Mental Wellbeing: Implications for Practice, Research, and Advocacy - Warria, Ajwang'; Chikadzi, Victor (African Human Mobility Review, 2023)
In 2016, the UNHCR estimated that about 10 million people, globally, were stateless. The issue of statelessness is inextricably linked to the psychosocial wellness and is a crucial mental health factor to consider in the holistic care, protection of stateless persons. There is a dearth of research examining the mental health implications for stateless persons and their exposure to multiple and ongoing rights violations. In addition, there is limited literature on the mental health impacts of statelessness. This paper describes the systematic human rights violations as linked to statelessness and how these contribute to individual trauma and stress – subsequently affecting wellbeing. The paper utilises a trauma-focused approach in understanding statelessness and presents a novel contribution to the research, advocacy and practice interventions addressing statelessness especially when drawing on the link between trauma and systemic rights violations.Findings from the document study reveal statelessness-linked stressors. Historic systematic human rights violations, traumatic events and situations, and previous and daily stressors become mental health burdens and challenges for those experiencing statelessness. Service providers working with stateless persons should be aware of the impact of statelessness on mental health and should refer cases to mental health practitioners who can provide services that reduce socio-emotional distress whilst strengthening resilience and coping strategies. The findings emphasize the promotion of stateless persons psychosocial wellbeing – looking at both curative and preventative strategies, towards the establishment of just and inclusive societies.